INTEGRATED FARM ENVIRONMENTAL MANAGEMENT AND BIODIVERSITY CONSERVATION: A CASE STUDY IN THE CARATINGA BIOLOGICAL STATION (MINAS GERAIS STATE, BRAZIL) GESTÃO AMBIENTAL DE ESTABELECIMENTOS RURAIS E CONSERVAÇÃO DA BIODIVERSIDADE: UM ESTUDO DE CASO NO ENTORNO DA ESTAÇÃO BIOLÓGICA DE CARATINGA (MG) - Geraldo Stachetti Rodrigues; Inácio de Barros; Cláudio César de Almeida Buschinelli; Jane Siqueira Lino; Janaína Mendonça Pereira (Pesquisa Agropecuária Tropical, 2010)
The Caratinga Biological Station (CBS) is an important preserve of the Brazilian Atlantic Rain Forest, defined as a national priority for the conservation of this highly fragmented biome and shelter to the largest existing population of the northern muriqui, the critically threatened largest monkey species of the Americas. Extensive research on the demography of this population has indicated favorable conditions for growth, pointing out the importance of promoting expansion of the locally available habitat. In the present study, rural establishments neighboring the CBS were involved in a participatory program for wildlife corridor restoration, by means of the application of a ‘System for Weighted Environmental Impact Assessment of Rural Activities’ (APOIA-NovoRural), which consists of 62 indicators integrated in five sustainability dimensions: i) Landscape ecology; ii) Environmental quality; iii) Socio-cultural values; iv) Economic values; and v) Management and administration. Results regarding the Landscape ecology indicators (those most related with fauna protection) attested to the adequate performance of productive activities in the studied establishments, while pointed out the need for improvements in natural habitats conservation. The Environmental Management Reports issued to the farmers included mapped recommendations for forest restoration and wildlife corridors implementation, favoring the connection of the main preserved area of CBS with the second largest forest fragment in the region. KEY-WORDS: Environmental Impact Assessment; rural development; wildlife corridors; APOIA-NovoRural. A Estação Biológica de Caratinga é uma importante reserva da Mata Atlântica, prioridade nacional para conservação do bioma, por abrigar uma das maiores populações do muriqui-do-norte, a maior espécie de primatas criticamente ameaçada das Américas. Estudos sobre a demografia desta população indicam condições favoráveis a um rápido crescimento, enfatizando a importância de se promover a expansão dos habitats localmente disponíveis. No presente estudo, estabelecimentos rurais vizinhos à reserva foram envolvidos em um programa participativo de recomposição de corredores de fauna, via gestão ambiental, com o sistema APOIA-NovoRural, que consiste de 62 indicadores integrados, em cinco dimensões de sustentabilidade: i) Ecologia da paisagem; ii) Qualidade ambiental; iii) Valores socioculturais; iv) Valores econômicos; e v) Gestão e administração. Os resultados relativos aos indicadores de Ecologia da paisagem (aqueles mais relacionados com a proteção da biodiversidade) demonstraram um adequado desempenho ambiental para as atividades produtivas, nos estabelecimentos estudados, enquanto, por outro lado, apontaram necessidade de melhorias na conservação dos habitats naturais. Relatórios de Gestão Ambiental produzidos nas avaliações e oferecidos aos produtores envolvidos incluíram mapeamento de recomendações para recomposição florestal e implementação de corredores de fauna, favorecendo a conexão da área principal da reserva com o segundo maior fragmento florestal existente na região. PALAVRAS-CHAVE: Avaliação de impacto ambiental; desenvolvimento rural; corredores de fauna; APOIA-NovoRural.